A nutritive dose of pure (–)-epicatechin does not beneficially affect increased cardiometabolic risk factors in overweight-to-obese adults—a randomized, placebo-controlled, double-blind crossover study. Issue 6 (4th June 2018) - Kirch, Natalie; Berk, Lea; Liegl, Yvonne; Adelsbach, Marcel; Zimmermann, Benno F; Stehle, Peter; Stoffel-Wagner, Birgit; Ludwig, Norbert; Schieber, Andreas; Helfrich, Hans-Peter; Ellinger, Sabine
ABSTRACT: Background: Regular cocoa consumption has been shown to reduce blood pressure, improve lipid profiles, and increase insulin sensitivity and flow-mediated dilatation in healthy adults. It is assumed that these effects can be attributed to polyphenolic cocoa ingredients such as flavanols, especially to (–)-epicatechin. Nutritive intervention studies to prove this hypothesis are scarce. Objective: We aimed to evaluate whether regular consumption of 25 mg of pure (–)-epicatechin can affect increased cardiometabolic risk factors [blood pressure, glucose and lipid metabolism, low-density lipoprotein (LDL) oxidation] in overweight-to-obese subjects. Design: Forty-eight overweight or obese nonsmokers [body mass index (kg/m 2 ) ≥25.0, ages 20–65 y] with clear signs of metabolic syndrome (blood pressure ≥130/85 mm Hg, glucose >5.55 mmol/L, or triglycerides >1.69 mmol/L or cholesterol >5.2 mmol/L in fasting blood) and without chronic diseases were included in a randomized, placebo-controlled, double-blind crossover study. Participants ingested daily 25 mg (–)-epicatechin (encapsulated) or placebo for 2-wk in random order (2-wk washout). After an overnight fast, blood pressure was monitored and blood samples were collected before and after both treatments. Anthropometric data were determined at each visit. Dietary intake was assessed by 3-d food records during both treatments and during run-in and washout phase. Results: Supplementation of pure (–)-epicatechin did not significantly affect blood pressure, glucose, insulin, homeostasis model assessment of insulin resistance, triglycerides, or total, LDL, or HDL cholesterol. Oxidized LDL, vitamins C and E, and β-carotene in plasma were not modulated. Body weight, fat mass, fat distribution, and the intake of energy, nutrients, and (–)-epicatechin from food remained stable throughout the study. Conclusions: Daily intake of 25 mg of pure (–)-epicatechin for 2 wk does not reduce cardiometabolic risk factors in overweight-to-obese adults. Thus, the hypothesis that the cardioprotective effects of regular cocoa consumption are exclusively ascribed to (–)-epicatechin should be reconsidered. The study was registered at the German Clinical Trial Register as DRKS-ID: DRKS00009846.